Improvement of regulatory and institutional framework of academia-industry knowledge transfer: experience of Ukraine, EU and USA - Khomenko, I.І.; Shakhbazian, K.S. (Наука, технології, інновації, 2017)
The article examines activities and structure of departments, involved in identification, protection of intellectual property rights, accumulation, storage of patent information, which in today's world is useful and valuable product, as far as given the great competition on the technology market and rapidly increasing level of technology, it is important to develop own technologies and to possess information on the direction of the competition.